Gastro Intestinal Parasites of Musk Deer (Moschus Chryso-Gaster Hodgson, 1839) in Langtang National Park, Nepal - Achhami, Bishnu; Sharma, Hari Prasad; Bam, Ashok Bahadur (Journal of Institute of Science and Technology, 2016)
This study was carried out to determine the prevalence of gastrointestinal parasites of musk deer in Langtang National Park, Nepal. A total of 9 fecal samples were collected systematically and analyzed using standard procedures during May-June, 2014. Overall 7 species of parasites including 4 nematodes, 1 cestode, 1 trematode and 1 protozoan parasite were recorded. Prevalence of Ascaris sp. was high (88.89%) followed by Eimeria sp. (77.78%), Trichuris sp. (66.67%), Strongyloides sp. (55.56%), Moniezia sp. (44.44%), Strongyle (44.44%) and Paramphistomum sp. (44.44%). Most of the samples had heavy parasitic infestation and multiple parasites were also observed in same individual. The high parasitic prevalence might have adverse health impact on musk deer. The possibility of cross-transmission of parasites between livestock and wildlife in Langtang National Park should be studied in future. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, Page: 71-75